Home to school transitions for financially disadvantaged children: Findings from LSAC Waves 1 and 2 - Edwards, B; Smart, D; Sanson, A; Baxter, Jennifer; Hayes, A (My University, 2009)
This paper presents findings from a study commissioned by The Smith Family and conducted by the Australian Institute of Family Studies, which aimed to identify key influences on Australian children's school readiness, particularly children in financially disadvantaged households. A range of child, family and broader environmental factors were found to be related to children's school readiness. When this set of variables was included together with family financial disadvantage (FD), financial disadvantage was seldom a unique predictor. Nevertheless, children from FD families were more likely to show low school readiness, due to the much higher rates of risk factors evident among this group. There was considerable commonality in the factors related to school readiness for children from FD and non-FD households. School readiness at 4-5 years was a powerful predictor of school achievement and adjustment at 6-7 years, and family FD increased the likelihood of poor progress in the literacy area. Findings are discussed in relation to two models proposed to explain links between FD and low school readiness: the family stress model, which appeared particularly relevant for social and emotional readiness; and the family investment model which appeared salient for learning and cognitive readiness.
Keywords: Finance -- Poverty and disadvantage; Education and Training -- Early Childhood; Finance; Education and Training; Learning, education and training; Income, wealth and finances; Education and Training; Finance; Poverty and disadvantage; Early Childhood; Income, wealth and finance; Learning, education and training